2021
DOI: 10.1016/j.jhep.2020.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived adenosine promotes macrophage proliferation in human hepatocellular carcinoma

Abstract: Background & Aims: Macrophages (Mu) represent a major component of tumor tissues and play an important role in both tumor progression and therapeutic response. Although tumor Mu are generally considered to be derived from circulating monocytes, emerging evidence indicates that tissue Mu pools can be maintained by self-renewal. We aimed to elucidate the contribution, phenotype, and regulatory mechanisms of proliferating Mu in human hepatocellular carcinoma (HCC). Methods: Flow cytometry analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 47 publications
0
60
0
Order By: Relevance
“…In addition, adenosine inhibits TNF-α and IL-12 release and augments IL-10 and vascular endothelial growth factor (VEGF) [ 122 ] production by LPS or bacteria-activated macrophages [ 123 , 124 , 125 , 126 ] and promotes alternative macrophage activation [ 127 ]. More recently, it has been reported that adenosine is also involved in TAMs proliferation [ 128 ]. Mechanistic studies have demonstrated that adenosine released from hepatoma cells could promote macrophages proliferation through the A2A receptor, and tumor-derived adenosine functions synergistically with autocrine GM-CSF released in TME, supporting macrophages proliferation ( Figure 2 ).…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, adenosine inhibits TNF-α and IL-12 release and augments IL-10 and vascular endothelial growth factor (VEGF) [ 122 ] production by LPS or bacteria-activated macrophages [ 123 , 124 , 125 , 126 ] and promotes alternative macrophage activation [ 127 ]. More recently, it has been reported that adenosine is also involved in TAMs proliferation [ 128 ]. Mechanistic studies have demonstrated that adenosine released from hepatoma cells could promote macrophages proliferation through the A2A receptor, and tumor-derived adenosine functions synergistically with autocrine GM-CSF released in TME, supporting macrophages proliferation ( Figure 2 ).…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…The activation of the IL-1β/IL-1R signaling pathway in tumors by TAMs is correlated with the acquisition of a CSC-like phenotype [ 96 ]. As observed in other tumor types, adenosine (ADO) pathways may be involved in MM cells-TAMs interaction, inducing the release of pro-tumoral cytokines and promoting TAMs proliferation [ 115 , 127 , 128 ]. Although limited data indicate its involvement in MPM immunosuppression [ 117 ], a deep investigation is required.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…COX regression analysis showed that ASF1B was an independent risk factor for HCC prognosis, and ROC curve analysis showed that ASF1B expression had certain predictive value for survival evaluation of HCC patients at 1, 3 and 5 years.ASF1B expression in HCC patients increased with tumor stage and grade progression, suggesting that ASF1B is associated with HCC disease progression. Recently, an increasing number of studies have found a correlation between cancer progression and tumor immune infiltration ( 30 , 31 ). Through public data mining, we also found a certain correlation between the expression of ASF1B and the immune infiltration of HCC, which is consistent with the conclusions of current reports ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is usually thought that TAM macrophages originate from blood monocytes [111], but in certain brain and lung (murine model animal) cancers, the tumors originated from tissue-resident macrophages [28]. M1-like TAM macrophages express CD68, CD80, CD86 and CD169 [110,112] and the M2-like class of TAM macrophages show strong CD204, CD206 and CD163 expression [112][113][114]. In addition, a new marker for these cells was recently found, the disulfide-isomerase A3 (PDIA3) receptor [115].…”
Section: Immunolabelingmentioning
confidence: 99%